Current chellenges that the Belarusian economy faces due to sanctions - Bogutskaya, V. O.; Solovieva, L. V. (ПолесГУ, 2023)
The article contains material on the concepts of «export» and «sanctions», as well as sanctions in the export of Belarus in the production of cars.